Piers, jetties and related structures exposed to waves guidelines for hydraulic loadings - McConnell, Kirsty (Thomas Telford, 2004)
Helps maritime designers to optimize jetty designs, and acts as an essential reference resource. This book provides guidance on hydraulic design, design wave conditions, prediction of scour and vessel mooring loads and methods for the prediction of wave loading.
Keywords: Hydraulic structures -- Design and construction.; Materials -- Dynamic testing.; elektronické knihy; electronic books